2016
DOI: 10.1016/j.cell.2015.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-type Identity of Proprioceptors Specified by Spatially Restricted Signals from Limb Mesenchyme

Abstract: The selectivity with which proprioceptive sensory neurons innervate their central and peripheral targets implies that they exhibit distinctions in muscle-type identity. The molecular correlates of proprioceptor identity and its origins remain largely unknown, however. In screens to define muscle-type proprioceptor character we find all-or-none differences in gene expression for proprioceptors that control antagonistic muscles at a single hindlimb joint. Analysis of three of these genes, cadherin13 (cdh13), sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 48 publications
1
74
0
Order By: Relevance
“…In this study, proprioceptive neuron specialization was neither affected by the MNs nor by muscle genetic ablation, pointing instead towards the contribution of mesenchymal cells. The identity of the regionalized mesenchyme-derived signals regulated by Lmx1b patterning activity, also remains unknown [88].…”
Section: Mesenchymal Fat1 Controls CM Muscle Growth and Impacts Mn Dementioning
confidence: 99%
“…In this study, proprioceptive neuron specialization was neither affected by the MNs nor by muscle genetic ablation, pointing instead towards the contribution of mesenchymal cells. The identity of the regionalized mesenchyme-derived signals regulated by Lmx1b patterning activity, also remains unknown [88].…”
Section: Mesenchymal Fat1 Controls CM Muscle Growth and Impacts Mn Dementioning
confidence: 99%
“…During locomotion, the CNS continuously elaborates the information coming from proprioceptors, a myriad of sensors (Poliak et al . ) located both in muscles (group Ia/II muscle spindles) and tendons (group Ib Golgi tendon organs, GTOs). It is well known that the loss of proprioceptive feedback may severely affect the motor function in mammals and is a symptom commonly associated with numerous neurological and orthopaedic conditions (Peterka, ; Konczak et al .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the ability to sense the position of own body parts in relation to the surrounding environment and the body itself, called proprioception, is of clear importance (Pearson, 1995). During locomotion, the CNS continuously elaborates the information coming from proprioceptors, a myriad of sensors (Poliak et al 2016) located both in muscles (group Ia/II muscle spindles) and tendons (group Ib Golgi tendon organs, GTOs). It is well known that the loss of proprioceptive feedback may severely affect the motor function in mammals and is a symptom commonly associated with numerous neurological and orthopaedic conditions (Peterka, 2002;Konczak et al 2009;Akay et al 2014;Fling et al 2014;Aman et al 2015;.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ΔR1,2 mice expressing only low Runx3 levels at E12.5 showed a later gain of Runx3 expression and exhibited no ataxia, although they did display locomotion defects in home cage and beam tests. Given that normal locomotion requires proper function of extensor and flexor muscles, which form connections with distinct TrkC subtypes (Poliak et al 2016), the fact that ΔR1,2 mice are not ataxic supports the notion of functional heterogeneity within this R3-only TrkC neuron subgroup. Moreover, given that R3 is less conserved than R1 (Supplemental Table S2), this subgroup may be associated with a phylogenetically more recent function of TrkC neurons.…”
Section: Combinatorial Re Cross-talk Regulates Runx3 In Different Trkmentioning
confidence: 81%
“…Using single-cell RNA-seq, two proprioceptive subtypes were detected in adult mouse DRGs (Usoskin et al 2015). It was also reported that mesenchymal signals expressed in restricted dorsoventral and proximodistal domains of the developing limb are essential for endowing muscle-type identity to two distinct proprioceptive subtypes, marked by the expression of either Cdh13, Sema5, or Crtac1 (Poliak et al 2016).…”
Section: Combinatorial Re Cross-talk Regulates Runx3 In Different Trkmentioning
confidence: 97%